Operative outcome of patients at low, intermediate, high and 'very high' surgical risk undergoing isolated aortic valve replacement with sutureless and rapid deployment prostheses: results of the SURD-IR registry. (25th January 2019) - Santarpino, Giuseppe; Berretta, Paolo; Fischlein, Theodor; Carrel, Thierry P; Teoh, Kevin; Misfeld, Martin; Savini, Carlo; Kappert, Utz; Glauber, Mattia; Villa, Emmanuel; Meuris, Bart; Mignosa, Carmelo; et al.
Abstract: OBJECTIVES: The ideal strategy for the treatment of severe aortic valve stenosis in patients of varying risk categories has become a debated topic in the last years: should the transcatheter or surgical approach be adopted? The aim of this study was to evaluate the outcomes of low-, intermediate-, high- and very high-risk patients undergoing sutureless, rapid deployment aortic valve replacement. METHODS: From 2007 to 2017, data on a total of 3651 patients were collected from the Sutureless and Rapid Deployment Aortic Valve Replacement International Registry (SURD-IR). Of these, 2057 patients who underwent primary isolated aortic valve replacement were considered for this analysis and classified as being at low (EuroSCORE <5; n  = 500), intermediate (EuroSCORE 5–10; n  = 901), high (EuroSCORE 11–20; n  = 500) and very high (EuroSCORE >20; n  = 156) preoperative risk. RESULTS: Overall, a less invasive approach was used in 74.1% of patients and represented the most frequent (>50%) approach in all risk categories. The Perceval prosthesis was used more frequently than other devices, especially in patients at high and very high risk. Hospital mortality was 1.6%, 0.8%, 1.9% and 2.7% in low-, intermediate-, high- and very high-risk patients, respectively, with no significant differences among subgroups. Similarly, postoperative complication rates were similar across the different risk categories. CONCLUSIONS: Surgical aortic valve replacement using sutureless, rapid deployment biological valve prostheses is associated with excellent results and represents a safe and effective treatment option for patients with severe aortic valve stenosis. This seems to be particularly true in patients with a higher risk profile.